2017
DOI: 10.24925/turjaf.v5i3.261-266.1038
|View full text |Cite
|
Sign up to set email alerts
|

Late Blight of Potato (Phytophthora infestans) I: Fungicides Application and Associated Challenges

Abstract: Potato (Solanum tuberosum L.) has been remained an important agricultural crop in resolving global food issues through decades. The crop has experienced enormous growth in terms of production throughout the world in recent decades because of improvement in agricultural mechanization, fertilizers application and irrigation practices. Nevertheless, a significant proportion of this valuable crop is still vulnerable to losses due to prevalence of different viral, bacterial, fungal and nematodes infestations. Late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
0
29
0
2
Order By: Relevance
“…In general, protectant fungicides application on potato foliage are made after 30 days of planting with additional successive applications every 7-10 days. Applications of systemic fungicides are made beginning 60 days after planting with up to 3 applications at 10 day intervals [39]. Nevertheless, it is also important to consider that late blight control should be based on an Integrated Disease Management (IDM) strategy, which in many opportunities is not the case for potato Colombian farmers.…”
Section: Discussionmentioning
confidence: 99%
“…In general, protectant fungicides application on potato foliage are made after 30 days of planting with additional successive applications every 7-10 days. Applications of systemic fungicides are made beginning 60 days after planting with up to 3 applications at 10 day intervals [39]. Nevertheless, it is also important to consider that late blight control should be based on an Integrated Disease Management (IDM) strategy, which in many opportunities is not the case for potato Colombian farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The uncontrolled use of fungicide doses and application may trigger an emergence of fungicideresistant P. infestans, and even more pathogenic that potentially spread out by emergence of heterothallic traits (Leesutthiphonchai et al, 2018;Majeed et al, 2017). It leads potato farmers to apply higher doses of fungicides to kill P. infestans.…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania and Morogoro, studies have shown that yield loss of tomato as a result of late blight disease infection is estimated to be up to 46% [5] while in Cameroon mean yield loss attributable to late blight damage is estimated to be as high as 100% [6]. In the world, late blight is one of the most devastating tomato disease which requires high chemical input for disease control [7]. Upon infection, most infected seedlings die and those that survive are stunted, have yellowish leaves and do not flower.…”
Section: Introductionmentioning
confidence: 99%